Evaluasi Kualitas Pelayanan Transportasi Jalan Di Kabupaten Nias Berdasarkan Persepsi Masyarakat Dan Aspek Manajemen Lalu Lintas - Laia, Bimawijaya; Zalukhu, Muhammad Haris; Daeli, Ikhtiar Aronifati (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to evaluate the quality of road transportation services in Nias Regency based on community perceptions and to examine the implemented traffic management aspects. A descriptive approach was employed using survey methods and field observations without conducting road capacity calculations. Data were collected through questionnaires distributed to 100 respondents, including motorcyclists, car drivers, public transport drivers, and pedestrians, as well as interviews with relevant agencies. The findings indicate that the overall quality of road transportation services is categorized as moderate, with several indicators such as safety, street lighting, and the availability of traffic signs and markings considered suboptimal. Traffic management aspects, particularly parking control and the handling of accident-prone areas, also require improvement. This study highlights that perception-based evaluation provides a comprehensive understanding of road transportation service conditions and can serve as a foundation for policy formulation aimed at improving infrastructure quality and sustainable traffic management.